Ipteks bagi Masyarakat Kelompok Tani Tanjung Saiyo dan Peternak Muda Ayam Kampung Super di Nagari Lolo Kecamatan Pantai Cermin Kabupaten Solok - Fitrini Fitrini; Montesqrit Montesqrit; Wazir Wazir (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2017)
Nagari lolo is an agricultural area that is dominated by rice fields so the main occupation of this village community is farming. Side jobs such as raising cattle and poultry. Partner devotion is Tanjung Saiyo farmer groups (rice farming and raising cattle) and breeder/ Ermita (raising chicken super). The purpose of this community service activities performed on both partners are providing sustenance to the practical science to both partners ranging from the technical aspects of cultivation, utilization of waste straw into cattle feed, chicken feed precise formulation, business planning until meat processing. Method of execution by means of education, discussion, demonstration, training and mentoring. Results devotion has been carried out as planned, by partner I: manufacture of straw fermentation, the manufacture of a feed processing, repair cowshed GFP standards and treatment of foot disease in cattle, cattle business plan development and manufacture of processed beef into nuggets, while the partner II : nursery and chicken hatching machine manufacture, manufacture of feed formulation chicken super precise, manufacture super chicken business plan, and the manufacture of processed chicken meat into meatballs. The success of visible activity of participation and cooperation given by both partners.